A functional study of denticulate sickles and knives, ground stone tools from the early Neolithic Peiligang culture, China. (June 2021) - Fullagar, Richard; Hayes, Elspeth; Chen, Xingcan; Ma, Xiaolin; Liu, Li
Abstract: Usewear analyses were undertaken on polyvinyl siloxane (PVS) peels from 23 Peiligang (9000–7000 cal BP) ground stone artefacts, including 20 with the denticulated cutting edges typical of implements called 'denticulate sickles' and three with cutting edges that lack denticulations, typical of implements called 'knives'. The denticulate sickles were recovered from three Peiligang sites including Jiahu, Shigu and Egou. The three knives were recovered from Jiahu. Patterns of polish and other usewear on denticulate sickles suggest that they were used for harvesting Poaceae grasses ( n = 5), cutting Typha cattails ( n = 1) or stripping tree branches to recover fruits or nuts ( n = 6). Five denticulate sickles were probably multi-functional tools, with traces of use suggesting combinations of these tasks. One of the knives has possible remnants of worn teeth and traces of use indicating harvesting Typha cattails. The function of three denticulate sickles and two knives is uncertain. Our evidence supports the hypothesis that denticulate sickles were multi-purpose tools, rather than specialised implements for harvesting cereals.